State planning of the tourism within the Chapada Diamantina as crisis management - Serrer, Pedro Benetazzo (Geografares, 2019)
The present article intends to retake aspects of the process of tourist modernization committed to the Chapada Diamantina as state planning and unfolding of the same. These particular elements are compared with a proposal of interpretation of the crisis of contemporary capitalist reproduction on a national scale and as a whole. Hence emerges the interpretation of planning as crisis management.
Keywords: Chapada Diamantina; crisis; planning; Brazil